Sputum cytology during late‐phase responses to inhalation challenge with different allergens. Issue 7 (6th February 2018) - Revez, J. A.; Killian, K. J.; O'Byrne, P. M.; Boulet, L.‐P.; Upham, J. W.; Gauvreau, G. M.; Ferreira, M. A. R.
Abstract: Background: In mouse models of allergic asthma, exposure to different allergens can trigger distinct inflammatory subtypes in the airways. We investigated whether this observation extends to humans. Methods: We compared the frequency of sputum inflammatory subtypes between mild allergic asthma subjects (n =   129) exposed to different allergens in inhalation challenge tests. These tests were performed using a standardized protocol as part of clinical trials of experimental treatments for asthma, prior to drug randomization. Five allergen types were represented: the house dust mites Dermatophagoides pteronyssinus and Dermatophagoides farinae, ragweed, grass, and cat. Results: Of 118 individuals with a sputum sample collected before allergen challenge (baseline), 45 (38%) had paucigranulocytic, 51 (43%) eosinophilic, 11 (9%) neutrophilic, and 11 (9%) mixed granulocytic sputum. Of note, most individuals with baseline paucigranulocytic sputum developed eosinophilic (48%) or mixed granulocytic (43%) sputum 7 hours after allergen challenge, highlighting the dynamic nature of sputum inflammatory subtype in asthma. Overall, there was no difference in the frequency of sputum inflammatory subtypes following challenge with different allergen types. Similar results were observed at 24 hours after allergen challenge. Conclusions: Unlike reported in mice, in humans the sputum inflammatory subtype observed after an allergen‐induced asthma exacerbation is unlikely to be influenced by the type of allergen used.